(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
The objective of this study was to determine the cause of weight variation of up to 60g in milk bags in an aseptic packaging machine, variables directly related to the weight of the bags were analyzed, leading to the determination that the cause was the horizontal sealing with Festo servo motors, the actuation and synchronization generated by the communication between the PLC and the servo motor controller were identified as the culprit, this system was homologated due to worldwide disruptions in the acquisition of technological equipment, as a result of identifying and correcting the system, a weight variation of +/-3g was achieved in the packaging, which aligns with quality standards, this improvement was attributed to the optimization of routine execution times and data packet transmission times.